Thrombopoietin mimetic therapy alleviates radiation-induced bone marrow vascular injury in a bone marrow transplant mouse model - Ghimire, Hemendra; Sargur Madabushi, Srideshikan; Vercellino, Justin; Brooks, Jamison; Zuro, Darren; Lim, Ji Eun; Vishwasrao, Paresh; Abdelhamid, Amr Mohamed Hamed; Strome, Guy; Eichenbaum, Gary; Al Malki, Monzr; Guha, Chandan; et al. (Frontiers in Oncology, 2024)
BackgroundThere is a need for therapies that can mitigate bone marrow dysfunction and organ toxicity that occur following myeloablative injury and reduced intensity conditioning regimens used in patients undergoing bone marrow transplantation (BMT). The pathogenesis of adverse effects from BMT conditioning has been linked to injury to the vascular endothelium, bone marrow (BM), and other organs.ObjectiveTo evaluate the impact of the thrombopoietin mimetic drug JNJ-26366821 (TPOm) on BM vascular recovery in mice undergoing myeloablative radiation conditioning followed by BMT.Study designTPOm (doses: 0 µg, 300 µg, 1000 µg per Kg body weight) was administered on Days 0 and 7 after BMT, in mice receiving a total body irradiation (TBI) conditioning regimen (5.5 Gy x 2) before congenic BMT. BM donner cell engraftment was analyzed using flow cytometry on Days 7, 14, and 30 post-BMT. The morphological and biophysical properties of the BM vasculature were evaluated by intravital multiphoton microscopy (MPM) and immunofluorescence confocal imaging. Herein, morphological properties involve microvascular density (MVD), vessel diameter, and vascular area, while biophysical properties include transfer rate (Ktrans) of contrast within the BM vascular niche, as well as the fractional volume (vec) of extracellular extravascular tissue (EES).ResultsNo significant difference in donor chimerism was observed at days 7, 14, and 30 post-BMT, between TPOm and PBS-treated mice. TPOm intervention improved BM vasculature regeneration in transplanted mice. The MVD, Ktrans, and BM vasculature as well as vascular endothelial growth factor receptor-2 (VEGFR2) in the BM, showed a dose dependent improvement in mice treated with TPOm. On day 14 post-BMT, the group receiving 1000 µg/Kg TPOm showed significant shifts (p-value < 0.05) in MVD, Ktrans, and VEGFR2 expression from their corresponding control types (TPOm dose 0 µg) towards levels comparable to healthy controls.ConclusionTPOm intervention augments BM vascular structure and function, which may be important for hematopoietic recovery and bone marrow function in radiation conditioned hematopoietic stem cell transplant patients, in addition to enhancing platelet recovery.